The relationship of pistol movement measured by a kinematic sensor, shooting performance and handgrip strength - Markovic, S.; Dopsaj, M.; Umek, A.; Prebeg, G.; Kos, A. (International Journal of Performance Analysis in Sport, 2020)
This paper aims to determine the relationship between the measures of shooting performance handgrip strength and weapon kinematics during different phases of the shot. The research included 35 participants who performed shooting sessions on 6 and 15 m shooting distance. Moderate (r > 0.388, p < 0.05) correlations were found between the handgrip strength and shooting performance. In the interval 1.0-0.1 s before the shot moderate correlations of weapon acceleration, accuracy and precision were determined (r > 0.310, p < 0.05) at the 6 m distance. Moderate correlations of shooting precision and rotational speed were found for the shooting distance 15 m for the same time interval (r > 0.413, p < 0.05). Moderate to high correlations of shooting accuracy, precision and weapon kinematics were found for both shooting distances (r > 0.405, p < 0.05) in the time interval 0.1-0.0 s. Absolute handgrip strength was a superior predictor of shooting performance than relative strength. Precision was more related to handgrip strength than accuracy and this relationship was more pronounced with distance. Correlations of shooting performance and rotational speed indicate high influence of the rotational component of weapon movement on the result.